A novel Ce(III)-imprinted polymer supported by attapulgite: synthesis, characterisation and adsorption behaviours towards Ce(III) in aqueous solution. (23rd November 2009) - Li, Chunxiang; Pan, Jianming; Gao, Jie; Yan, Yongsheng
The surface ion-imprinting concept and chitosan incorporated sol-gel process were applied to the synthesis of a new attapulgite-supported polymer for selective separation of Ce(III) from aqueous solution. The prepared Ce(III)-imprinted polymer was characterised with SEM, IR and XRD, and the results showed that it had good configuration and binding sites. Then the adsorption behaviours towards Ce(III) were investigated by fluorescence spectrophotometry and ICP-AES. The effects on adsorption capacities which include pH, quiescent time and mass of sorbent were discussed. Adsorption isothermal was also obtained. Under the optimum conditions, Ce(III)-imprinted polymer offered a fast kinetics for the adsorption of Ce(III) and the maximum capacity was 38.02 mgg−1. Then the Kd, K and K′ parameters, estimating relative adsorption for target ion, suggested that selective recognition of Ce(III)-imprinted polymer was much higher than that of the non-imprinted polymer and attapulgite. Furthermore, the Ce(III)-imprinted polymer was capable of great regeneration capacity. The prepared functional polymer was shown to be promising for selective pre-separation and enrichment of trace Ce(III) in environmental samples.